2020
DOI: 10.1111/cas.14711
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of BIM deletion polymorphism in chemoradiotherapy for non‐small cell lung cancer

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Recent evidence also shows that selective targeting of these pathways has cytotoxic effects on cancer stem cells (See Table 2). (Bolomsky et al, 2020) Bcl family proteins/gene silencing (i) Bcl-2 siRNA and antisense nucleotides (Gagliardi and Ashizawa, 2022;Meng et al, 2015) (ii) Bim-1 siRNA (Schwulst et al, 2008;Wakabayashi et al, 2021) Targeting p53…”
Section: Drugs Targeting Autophagymentioning
confidence: 99%
“…Recent evidence also shows that selective targeting of these pathways has cytotoxic effects on cancer stem cells (See Table 2). (Bolomsky et al, 2020) Bcl family proteins/gene silencing (i) Bcl-2 siRNA and antisense nucleotides (Gagliardi and Ashizawa, 2022;Meng et al, 2015) (ii) Bim-1 siRNA (Schwulst et al, 2008;Wakabayashi et al, 2021) Targeting p53…”
Section: Drugs Targeting Autophagymentioning
confidence: 99%
“…BIM, also known as B-cell chronic lymphocytic leukemia/lymphoma (Bcl-2)-like 11, encodes BCL2L11, which is a member of Bcl-2 protein family. BIM deletion polymorphism, resulting from the 2903-bp genomic deletion occurring in intron 2 of BIM gene, is commonly seen in East Asian and Hispanic patients with EGFR -mutant lung cancer with an incidence rate of 11.3–18.6% ( 8 , 9 ). Some studies reported that BIM deletion polymorphism predicted an unfavorable prognosis in EGFR -mutant NSCLC patients when treated with EGFR-TKIs ( 8 , 10 - 12 ), but other studies failed to find an association between the presence of BIM deletion polymorphism and the clinical outcome in these patients ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…BIM deletion polymorphism, resulting from the 2903-bp genomic deletion occurring in intron 2 of BIM gene, is commonly seen in East Asian and Hispanic patients with EGFR -mutant lung cancer with an incidence rate of 11.3–18.6% ( 8 , 9 ). Some studies reported that BIM deletion polymorphism predicted an unfavorable prognosis in EGFR -mutant NSCLC patients when treated with EGFR-TKIs ( 8 , 10 - 12 ), but other studies failed to find an association between the presence of BIM deletion polymorphism and the clinical outcome in these patients ( 13 , 14 ). Moreover, an array of studies have demonstrated that increased BIM at the RNA level enhances killing of NSCLC cells by the EGFR-TKIs, which contributes to the molecular mechanisms leading to tumor regression ( 15 - 18 ).…”
Section: Introductionmentioning
confidence: 99%